Hibah dalam Sistem Pembagian Waris Islam - Fetri Fatorina (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2021)
The concept of wealth in the perspective of ‘ilm faraid has been explained in detail to understand the people regarding the concept of Islamic inheritance. However, in practice, several people divide the inheritance before the heir died. They believe that the assets given by parents, before they died or already died can be categorized as inheritance, not gifts. The purpose of this study is to determine the status of the assets in the Islamic inheritance distribution system. This research is a library research with descriptive-comparative analysis method between fiqh and Islamic Law Compilation (KHI) related to the position of grants in the Islamic inheritance law. The results showed that the grant from parents to their children could not be considered as inheritance when considering the concept of Islamic inheritance and its elements. It is more precisely known as hibah. Even so, a gift from parents can be said to be an inheritance if it refers to the clause in KHI article 211. So it can be said that the inheritance distribution system using the grant channel is legal.